How Inclusive Hospitality Organizational Culture (IHOC) Drives Employee Service Outcomes through Psychological Safety and Job Satisfaction in Five-Star Hotels in Yogyakarta - Nazmah; Agus Setiono; Zuraida; Maidiana Astuti Handayani; Esty Pudyastuti (Fundamental and Applied Management Journal, 2026)
This study examines the relationships between Inclusive Hospitality Organizational Culture (IHOC) and employee service outcomes in five-star hotels in Yogyakarta, with Psychological Safety and Job Satisfaction serving as parallel mediating mechanisms. Grounded in Social Exchange Theory, this study explores how inclusive cultural practices are associated with employee behavioral outcomes in highly competitive hospitality environments. Data were collected from 346 employees working in seven five-star hotels in Yogyakarta, and the proposed model was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that IHOC is positively associated with Psychological Safety and Job Satisfaction, which in turn are associated with higher levels of Employee Loyalty, Employee Engagement, and Service Quality. Furthermore, the findings revealed that IHOC influences employee outcomes through both direct and indirect pathways, supporting a partial mediation model. The mediation analysis demonstrates that Job Satisfaction serves as a stronger mediating mechanism, particularly in explaining Employee Engagement and Service Quality, while Psychological Safety contributes more strongly to Employee Loyalty and Service Quality. These findings highlight the important roles of psychological safety and job satisfaction in translating an inclusive organizational culture into positive employee service outcomes within five-star hotel settings.